MRI Evaluation of Rhino-orbito-cerebral Mucormycosis in Post COVID-19 Patients: A Cross-sectional Study - Siddappa Ramappa Shirahatti; KS Prashanth; Eranna Palled; RC Sudhakar (International Journal of Anatomy Radiology and Surgery, 2022)
Introduction: Mucormycosis is the common cause of invasive fungal sinusitis in post Coronavirus Disease-2019 (COVID-19) patient. Mucormycosis is a life-threatening infection with a death rate of >50%. Early detection is critical for determining the amount of infection dissemination, as medical and surgical intervention can reduce death and morbidity.